A Multimodal Discourse Analysis on a Music Video: "Confetti" by Little Mix ft. Saweetie - Annisa Kharismi; Fitrawati Fitrawati (English Language and Literature, 2023)
Music video as a discourse demands the expression of meaning-making encoded which can be apprehended from many aspects of analysis including visual pattern and language used. This research takes a music video from Little Mix ft. Saweetie for their song Confetti which represents gender stereotypes issue of three genders: male, female, and queer. This study aims to, 1) reveal the representational meaning in visual pattern  constructed in Confetti music video based on gender categorized (male, female, and queer) and 2) investigate the language used based on gender categorized (male, female, and queer) on the skit of Confetti music video revealed by using interpersonal metafunction. The writer used descriptive-qualitative method based on representational meaning in semiotic approach theory by Kress and van Leeuwen (2006) and the interpersonal metafunction in SFL theory by Matthiessen and Halliday (2004). The results showed gender stereotypes of male, female, and queer in narrative process (including actional and reactional processes, and locative circumstances) and conceptual processes (including classificational process, analytical processes, and symbolic processes). In language used related to interpersonal metafunction, the dominant mood functions used by male and female is declarative mood, while queer are indicated with mostly no mood functions founded in exclamatory sentences form.